Étude des conditions du développement professionnel d’enseignants du premier degré. Genèse de gestes professionnels et pragmatisation de concepts didactiques - Virginie Billon; Caroline Bulf; Martine Champagne; Lalina Coulange; Yann Lhoste (Recherches en Éducation)
This article aims to present the first results of our research describing some processes related to professional development of future teachers. From a large set of data (filmed visits, business reports, professional writing, etc.) we highlight some salient features of beginning teachers practices, under certain didactic concepts worked on in training. We follow the evolution of certain teaching skills in the practice of beginning teachers on a year of training. This allows us to formulate hypotheses about the conditions and constraints on the development of certain teaching skills that we will seek to realize in terms of "pragmatization" in the sense of P. Pastré or conceptualization of educational concepts.